An Exploration of Collaborative Economy Entrepreneurs in the Tourism Industry through the Novel Prism of Epistemic Culture - Sibbritt, Karon; Volgger, Michael; Weber, Paull; Geneste, Louis (Elsevier, 2019)
This paper presents a conceptual framework derived from Knorr-Cetina’s (1999) theory of Epistemic Culture (EC) and uses it to catalogue and explore what she described as the “machineries of knowing”. The conceptual framework is explicated via empirical analysis of a case of an emergent group of collaborative economy entrepreneurs (CEEs) and their ventures operating in the tourism industry. Based upon qualitative interviews with property owners/managers as CEEs, this study builds further upon an a-priori proposed typology of EC Machineries of Knowing (MOK) and then explores the possible influence of such MOKs upon participating entrepreneurs. The exploration of ECs in the particular setting of the collaborative economy focusses attention upon how epistemic cultures form a specific entrepreneurial ecosystem and how they inter-relate with typologies of entrepreneurs. This fresh conceptual approach is shown to have good explicatory qualities that are capable of unlocking the “black box” that is collaborative economy entrepreneurship.